Xinjiang porcelain glaze and porcelain preparation method
By using glaze formulas based on Xinjiang Santanghu porcelain stone and calcite and feldspar, along with a phased reduction firing process, the problem of matching Xinjiang porcelain stone with traditional glaze formulas has been solved. This has resulted in high-quality porcelain with distinctive regional hues, supporting the development of Xinjiang's ceramic industry.
Patent Information
- Application Number
- CN202511514236.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-22
- Publication Date
- 2026-01-06
AI Technical Summary
The chemical composition of Xinjiang porcelain stone differs from that of traditional famous porcelain raw materials, making it difficult to match glaze formulas and firing processes. This results in glaze cracking, glaze flow, or uneven crystallization. Furthermore, the lack of a suitable firing regime makes it difficult to unleash the color potential and achieve the industrial production of high-quality porcelain.
Using Xinjiang Santanghu porcelain stone as the main raw material, combined with calcite and feldspar, the glaze formula was designed and a phased reduction firing process was used to control the flow of the glaze layer and the change of atmosphere, forming a color tone with Xinjiang regional characteristics.
It has enabled the production of high-quality porcelain with a lustrous, crack-free glaze, featuring regional colors characteristic of deserts, Gobi, and grasslands, supporting the large-scale and distinctive development of Xinjiang's ceramic industry.
Smart Images

Figure CN121270097A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic materials and preparation technology, specifically to a porcelain glaze using local mineral resources in Xinjiang as the core raw material and a method for preparing porcelain using the porcelain glaze. Background Technology
[0002] Xinjiang boasts abundant ceramic mineral resources, with the porcelain stone produced in Santanghu Town, Barkol County, Hami City, being a prime example. Its chemical composition is characterized by high silicon and high aluminum content, and it also contains coloring elements such as iron and titanium, giving it the potential to serve as a base raw material for porcelain glazes. Developing and utilizing these local mineral resources will not only help promote the high-quality development of the regional ceramic industry but also play a significant role in shaping a ceramic cultural brand with distinctive Xinjiang characteristics.
[0003] However, systematic research on this resource in the field of high-end porcelain is still insufficient, and its industrialization faces significant technical bottlenecks. Due to the inherent differences in chemical composition and physical properties between Xinjiang porcelain stone and the raw materials relied upon by traditional famous porcelains (such as Ru ware), it is difficult to directly transplant traditional mature glaze formulas and firing processes to achieve the desired porcelain-making effect. Specific technical difficulties include: (1) Traditional glaze formulas have low compatibility with Xinjiang porcelain stone components. Direct application can easily cause key parameters such as glaze melting temperature, viscosity and thermal expansion coefficient to deviate from the reasonable range, thus causing defects such as glaze cracking, glaze flow or uneven crystallization. (2) The types and contents of coloring elements such as iron and titanium contained in Xinjiang minerals are different from those of traditional raw materials. There is a lack of suitable firing system (especially atmosphere conversion and temperature curve), making it difficult to stably stimulate their coloring potential and achieve the glaze kiln transformation effect that combines the texture of traditional famous porcelain with the regional characteristics of Xinjiang (such as the colors of desert, Gobi and grassland). (3) A complete and controllable industrial production process system from raw material processing and glaze processing to firing system has not yet been established, which means that the preparation of high-quality porcelain using Xinjiang porcelain stone is still mostly in the experimental stage and it is difficult to achieve large-scale and standardized production.
[0004] Therefore, there is an urgent need in this field to develop a glaze formula designed specifically for the mineral characteristics of Xinjiang, and to develop a standardized and reusable preparation process to support the stable production of high-quality porcelain and promote the value enhancement and industrial application of Xinjiang ceramic resources. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of existing technologies where local Xinjiang porcelain stone is difficult to adapt to traditional glaze formulas and firing processes, thus hindering the industrial production of high-quality porcelain. This invention provides a method for preparing Xinjiang porcelain glaze and porcelain. Using local Xinjiang Santanghu porcelain stone as the main raw material, this method, through innovative glaze formula design and standardized preparation and firing processes, stably produces high-quality porcelain with a lustrous glaze, distinctive Xinjiang regional colors (desert, Gobi, and grassland colors), and excellent performance. Ultimately, this achieves localization of raw materials, standardization of processes, and product specialization, providing technical support for the upgrading and development of Xinjiang's ceramic industry.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: On the one hand, the present invention provides a Xinjiang porcelain glaze, the raw material composition and its mass percentage of the Xinjiang porcelain glaze are as follows: Santanghu porcelain stone contains 70%-80%; Calcite 9%-15%; White feldspar 6%-8%; The sum of the mass percentages of the raw materials is 100%.
[0007] Furthermore, the Santanghu porcelain stone comprises the following components in the following mass ratio: Fe2O3 2.95%, MnO 0.06%, TiO2 0.29%, CaO 10.91%, K2O 2.30%, Al2O3 5.33%, SiO2 38.80%, MgO 4.84%, with the balance being impurities.
[0008] Furthermore, calcite comprises the following components in the following mass ratio: CaO 55.87%, CO2 43.28%, MgO 0.27%, SiO2 0.38%, Fe2O3 0.09%, Al2O3 0.1%, with the balance being impurities.
[0009] Furthermore, the white feldspar comprises the following components in the following mass ratio: SiO2 65.83%, Al2O3 18.94%, K2O 10.10%, Na2O 4.23%, Fe2O3 0.39%, and loss on ignition 0.51%.
[0010] On the other hand, the present invention provides a method for preparing porcelain using the above-mentioned Xinjiang porcelain glaze, which mainly includes the following steps: (1) Preparation of basic glaze: After beneficiation and washing of Santanghu porcelain stone, it is dried. Calcite, feldspar and washed Santanghu porcelain stone are crushed to a particle size of 50-100 mesh. The crushed raw materials are weighed according to the above mass percentage and mixed for 0.5 hours to obtain the basic glaze. (2) Glaze slurry preparation: Add deionized water to the base glaze and ball mill for 13-14 hours using a wet ball milling process to achieve a glaze slurry fineness of 200 mesh with a sieve residue of <0.5%. Add deionized water to the glaze slurry or allow it to stand and concentrate to adjust the glaze slurry specific gravity to 1.4-1.5 g / cm³. 3 Stir well and set aside. (3) Glazing: Dry the ceramic body at 28-80℃ for 2-4 hours, apply the glaze slurry to the surface of the ceramic body by immersion glazing or spray glazing, control the glaze thickness to be 0.1-0.5mm, and let it stand for 10 minutes to drain after glazing. (4) Firing: The firing process is divided into the following five stages: First stage: heating from 0℃ to 500℃ at a rate of 5-15℃ / min, firing in an oxygen atmosphere; The second stage: heating from 500℃ to 1000℃ at a rate of 10-15℃ / min, and firing in an oxygen atmosphere; The third stage: the temperature is raised from 1000℃ to 1300℃ at a rate of 10-15℃ / min, and the temperature is then fired in a reducing atmosphere; Fourth stage: Keep warm at 1300℃ for 0.5 hours; Fifth stage: Cool to room temperature in the kiln to obtain the finished porcelain.
[0011] Furthermore, in step (3), the ceramic body is made of kaolin.
[0012] Furthermore, in step (4), the reducing atmosphere is a CO atmosphere with a CO concentration of 1.5-2.5%.
[0013] The porcelain prepared by this invention can exhibit the typical geographical environment colors of Xinjiang (desert colors, Gobi colors, grassland colors), and its core mechanism is as follows: (1) Colorant basis: The iron element contained in the body (kaolin) and glaze (mainly Santanghu porcelain stone) is used as the reducing colorant. The change of the valence state of the iron element is the core of color formation. (2) Glaze flow control: During the glazing process, according to the different characteristics of the porcelain shape (such as the concave and convex parts and turning parts of the shape), the glaze thickness and flow trend of each part of the control shape are controlled by adjusting the glazing time (glazing method) or the glazing pressure (glazing method), laying the foundation for the formation of different colors in different parts later. (3) Synergistic effect of atmosphere and temperature: In the five stages of the firing process (especially the reduction firing stage), by continuously changing the gap of the kiln gate (the size of the gate gap can adjust the air intake and exhaust volume in the kiln, thereby controlling the concentration of atmosphere components), the timing of the conversion between oxidizing and reducing atmospheres in the kiln is precisely controlled, so that the valence state of iron changes under different temperature and atmosphere conditions (Fe 3+ with Fe2+ (The proportion is adjusted); at the same time, the flow of the glaze at high temperature will cause local differences in iron concentration, ultimately forming a rich kiln transformation effect and presenting a color tone with Xinjiang regional characteristics.
[0014] The beneficial effects of this invention are: (1) This invention innovatively uses local Xinjiang Santanghu porcelain stone as the main glaze material (accounting for 70%-80%), making full use of its advantages of high silicon, high aluminum and unique iron and titanium elements. Combined with a staged reduction firing process (especially the control of CO concentration of 1.5-2.5% in the 1300℃ reduction stage), the coloring potential of iron elements is stably stimulated, and porcelain with Xinjiang regional characteristics (desert color, Gobi color, grassland color) is fired. This product fills the gap in Xinjiang's history of not having high-temperature art porcelain and daily-use porcelain, and provides a core carrier for the shaping of Xinjiang's ceramic culture brand.
[0015] (2) Through scientific raw material ratio (synergistic application of Santanghu porcelain stone-calcite-feldspar) and optimized firing process, the porcelain glaze quality prepared by this invention is significantly superior to that of the prior art: Synergistic effect of raw material ratio: Santanghu porcelain stone provides basic glaze and coloring elements, calcite can lower the melting temperature of glaze and regulate the fluidity of glaze layer, and feldspar can improve the transparency and gloss of glaze layer. The three work together to make the glaze surface lustrous and rich in color, with a warm and smooth texture similar to traditional Ru porcelain. The Guarantee Role of the Five-Stage Firing System: The firing system designed in this invention systematically guarantees glaze quality and yield through five precisely controlled stages: Stage 1 (0℃-500℃): Stable dehumidification effectively removes physical and adsorbed water from the body and glaze layer, preventing subsequent rapid heating that could lead to cracking of the body or peeling of the glaze layer. Stage 2 (500℃-1000℃): Under an oxidizing atmosphere, organic matter and carbonates in the body are thoroughly decomposed, and crystalline and structural water is discharged, fundamentally avoiding defects such as glaze bubbles and pinholes caused by residual gases. Stage 3 (1000℃-1300℃) and Stage 4 (1300℃ holding): Under a reducing atmosphere, the glaze completely melts, and coloring elements such as iron are reduced and stably precipitated, forming unique regional hues such as "desert, Gobi, and grassland"; at the same time, the holding stage promotes full reaction and bonding at the interface between the glaze layer and the body, allowing for a better match between their coefficients of thermal expansion. The fifth stage (cooling with the kiln): the glaze layer is controlled to crystallize and solidify at a stable cooling rate to form a stable glass phase, thereby finally obtaining finished porcelain with no cracks or peeling and excellent high-temperature stability.
[0016] (3) The preparation method provided by this invention (from basic glaze preparation to firing) has clear and controllable parameters for each step, specifically as follows: The raw material pretreatment parameters are clearly defined: the Santanghu porcelain stone is washed until the washing liquid is clear, the particle size is 50-100 mesh, and the mixing time is 0.5 hours to ensure that the raw material impurities are thoroughly removed and the mixture is uniform; The glaze slurry parameters are controllable: ball milling time 13-14 hours, glaze slurry fineness 200 mesh (sieve residue <0.5%), specific gravity 1.4-1.5 g / cm³. 3 This ensures stable glaze quality and avoids glazing defects. Standardized firing parameters: The temperature range, heating rate, firing atmosphere, and holding time for different stages are all clearly defined, allowing for precise control through industrial kilns and avoiding the randomness of laboratory processes. These standardized processes can be directly applied to industrial production lines, enabling the mass production of high-quality Xinjiang porcelain and providing technical support for the large-scale development of Xinjiang's ceramics industry.
[0017] (4) This invention takes Xinjiang Santanghu porcelain stone (a resource from a non-traditional ceramic raw material production area) as its core, and through targeted formula design (adapting to the raw material composition) and process optimization (adapting to the raw material characteristics), successfully develops high-quality ceramic products. This technical approach breaks the traditional ceramic industry's dependence on raw materials from specific production areas, and provides a feasible technical path for developing high-quality ceramic products from other non-traditional ceramic raw material production areas (such as areas containing minerals with special coloring elements), and has broad promotion and application value. Attached Figure Description
[0018] Figure 1 This is one of the effect images of the porcelain glaze sample prepared in Example 1.
[0019] Figure 2 This is the second effect image of the porcelain glaze sample prepared in Example 2.
[0020] Figure 3 The third image shows the effect of the porcelain glaze sample prepared in Example 3. Detailed Implementation
[0021] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.
[0022] First, this invention provides a Xinjiang porcelain glaze, the raw material composition and the mass percentage of each raw material are as follows: Santanghu porcelain stone: 70%-80%; Calcite: 9%-15%; White feldspar: 6%-8%; The sum of the mass percentages of the above three raw materials is 100%.
[0023] The specific chemical composition (by mass ratio) of each raw material is as follows: Santanghu porcelain stone: Fe2O3 2.95%, MnO 0.06%, TiO2 0.29%, CaO 10.91%, K2O 2.30%, Al2O3 5.33%, SiO2 38.80%, MgO 4.84%, with the remainder being impurities.
[0024] Calcite: CaO 55.87%, CO2 43.28%, MgO 0.27%, SiO2 0.38%, Fe2O3 0.09%, Al2O3 0.1%, with the balance being impurities.
[0025] White feldspar: SiO2 65.83%, Al2O3 18.94%, K2O 10.10%, Na2O 4.23%, Fe2O3 0.39%, Loss on ignition 0.51% (Loss on ignition refers to the mass loss that occurs when the raw material is ignited at high temperature, mainly including moisture, carbonate decomposition, etc.).
[0026] Next, the present invention provides a method for preparing porcelain using the above-mentioned porcelain glaze. The method for preparing porcelain using the above-mentioned Xinjiang porcelain glaze mainly includes four steps: preparation of basic glaze, preparation of glaze slurry, glazing, and firing. Each step is described in detail below.
[0027] Step (1) Preparation of basic glaze The core function of this step is to pre-treat and precisely mix the raw materials, remove impurities, and ensure the uniformity of the raw material components, laying the foundation for the subsequent glaze quality and glazing effect. Specifically, this includes: Step (1-1), Mineral Selection and Washing: The Xinjiang Santanghu porcelain stone is selected manually or mechanically. Impurities such as mud and stones mixed in the raw material are removed by screening and hand selection (impurities will cause defects such as spots and pinholes on the glaze). Then, the selected porcelain stone is washed with clean water until the washing liquid is clear (indicating that the mud impurities have been basically removed). The washed porcelain stone is dried for later use to avoid the moisture affecting the uniformity of subsequent crushing and mixing. Steps (1-2), Crushing: Calcite, feldspar, and washed Santanghu porcelain stone are crushed separately using a stone mill or ball mill, controlling the particle size of all raw materials to be 50-100 mesh. The design basis for this particle size range is: if the particle size is too coarse, it will be difficult to achieve the required fineness of the glaze slurry in subsequent ball milling, easily resulting in a rough glaze surface and uneven crystallization; if the particle size is too fine, it will increase the energy consumption of crushing and may cause the raw materials to clump during the mixing process, affecting the uniformity of mixing; Steps (1-3), Mixing: Accurately weigh each pulverized raw material according to the above-mentioned raw material mass percentages for the porcelain glaze (70%-80% Santanghu porcelain stone, 9%-15% calcite, 6%-8% feldspar); put the weighed raw materials into a mixer and mix for 0.5 hours until the material has a uniform color and feel, thus obtaining the basic glaze. The 0.5-hour mixing time ensures that the raw materials are fully mixed (avoiding glaze defects caused by local component deviations) and also avoids energy waste and raw material wear caused by over-mixing.
[0028] Step (2) Glaze preparation The purpose of this step is to prepare the base glaze into a glaze slurry with suitable fineness and concentration, ensuring that the glaze layer is uniform and tightly bonded to the body after glazing. Specifically, this includes: Step (2-1), Ball Milling: Add deionized water to the base glaze (to avoid impurities in the water affecting the composition and color of the glaze slurry), and grind using a wet ball milling process. During ball milling, control the mass ratio of material (base glaze): balls (grinding balls): water to 1:2:0.8-1.2, and set the ball milling time to 13-14 hours. This time ensures that the fineness of the glaze slurry reaches 200 mesh (tested using a standard sieve, with a sieve residue of <0.5%). A fineness of 200 mesh is key to ensuring a lustrous glaze surface: insufficient fineness (sieve residue >0.5%) will result in coarse glaze particles, making the glaze surface prone to a grainy feel and pinholes after glazing; excessive fineness will result in excessively viscous glaze slurry, making the glaze layer too thick and causing glaze runs during glazing. Step (2-2), Concentration Adjustment: After ball milling, check the specific gravity of the glaze slurry. If the specific gravity is too high (>1.5g / cm³), 3 If the specific gravity is too low (<1.4 g / cm³), then add deionized water to dilute it; if the specific gravity is too low (<1.4 g / cm³), then add deionized water to dilute it. 3 Then, the glaze slurry is allowed to stand and concentrate (using gravity to allow the glaze particles to settle and remove some of the clear water from the top); finally, the specific gravity of the glaze slurry is adjusted to 1.4-1.5 g / cm³. 3 Stir well and set aside. Glaze slurry within this specific gravity range has suitable fluidity, which can ensure that the glaze layer evenly covers the surface of the body during glazing, and avoid uneven glaze layer thickness caused by excessive flow of the glaze slurry after glazing.
[0029] Step (3) Glazing The purpose of this step is to evenly cover the surface of the ceramic body with glaze slurry, forming a complete and uniform glaze layer, which prepares for subsequent firing to form a high-quality glaze surface. Specifically, this includes: Step (3-1), Pretreatment: The ceramic body is made of kaolin (kaolin has good plasticity and sintering properties, and is a commonly used raw material for traditional high-end porcelain bodies). The body is dried at 28℃-80℃ for 2-4 hours. The purpose of drying is to remove moisture from the body: if the moisture content of the body is too high, rapid evaporation of moisture during subsequent firing will cause the body to crack and the glaze to peel off; the drying temperature of 28℃-80℃ is low-temperature drying, which can avoid high-temperature drying causing stress concentration inside the body (causing cracking); the drying time of 2-4 hours can be adjusted according to the thickness of the body (thick body requires a longer drying time, thin body requires a shorter drying time) to ensure that the moisture content of the body is reduced to below 5%; Step (3-2), Glazing operation: Apply the glaze slurry to the surface of the dried body using the dipping or spraying method; control the glaze thickness to 0.1-0.5mm. After glazing, let the body stand for 10 minutes to drain excess glaze slurry. A glaze layer thickness of 0.1-0.5mm is the optimal range considering both the glazing effect and the adhesion to the body: too thin a thickness (<0.1mm) will result in an incomplete glaze layer after firing, easily exposing the body; too thick a thickness (>0.5mm) will result in excessive shrinkage of the glaze layer during firing, causing cracking and glaze run-through; letting it stand for 10 minutes allows excess glaze slurry to drip off naturally, avoiding excessively thick glaze layers in some areas, while also ensuring sufficient contact between the glaze slurry and the body surface, improving the bonding tightness.
[0030] Step (4) Firing Firing is a crucial step in the formation of porcelain. Through staged temperature and atmosphere control, the body is sintered and the glaze melts and colors, ultimately creating "Xinjiang porcelain" with distinctive regional characteristics. This process is divided into five stages: Step (4-1), First Stage: The temperature is raised from 0℃ to approximately 500℃, with a heating rate controlled at 5-15℃ / min, and fired in an air atmosphere. The core function of this stage is to remove moisture from the body and glaze: slow heating at low temperature (5-15℃ / min) allows moisture to evaporate slowly, preventing rapid moisture escape that could cause cracking of the body and separation of the glaze from the body; an oxidizing atmosphere (oxygen in the air) can assist in moisture evaporation while preventing undesirable chemical reactions between the body and glaze at low temperatures; Step (4-2), Second Stage: The temperature is raised from 500℃ to 1000℃ at a rate of 10-15℃ / min, and fired in an air atmosphere. The main purpose of this stage is to remove organic matter and carbonates from the body: the small amount of organic matter in the body (kaolin) is oxidized and decomposed into gases such as CO2 and H2O at 500℃-1000℃ and escapes; CO2 in calcite will also decompose and escape in this temperature range; the oxygen in the air can ensure that the organic matter and carbonates are fully oxidized and decomposed (avoiding residues that may cause bubbles and pinholes on the glaze), and the heating rate of 10-15℃ / min can prevent stress cracking of the body due to a sudden temperature rise; Step (4-3), Third Stage: The temperature is raised from 1000℃ to 1300℃ at a rate of 10-15℃ / min, and fired in a reducing atmosphere (CO concentration of 1.5-2.5%). This stage is crucial for glaze melting, color development, and body sintering: 1300℃ is the high-temperature sintering temperature, which allows components such as SiO2 and Al2O3 in the glaze to fully melt, forming a continuous and uniform glaze layer; the reducing atmosphere (CO as a reducing agent) can separate the Fe in the glaze and body. 3+ Reduced to Fe 2+ (Fe) 2+ It is the core coloring ion that forms the distinctive hues of Xinjiang; a CO concentration of 1.5-2.5% can stably control Fe. 3+ To Fe 2+ The reduction reaction (if the concentration is too low, the reduction will be insufficient and the color will be dull; if the concentration is too high, metallic iron spots may appear on the glaze). Step (4-4), fourth stage: Hold at 1300℃ for 0.5 hours. The 0.5-hour holding time ensures that the glaze layer is fully melted and flows evenly, while also forming a good bonding interface between the body and the glaze layer; Steps (4-5), the fifth stage: Cooling with the kiln to room temperature to obtain the finished porcelain. Cooling with the kiln can avoid sudden temperature drops that could cause glaze cracking and body deformation.
[0031] The technical solution of the present invention will be described in detail below with reference to specific embodiments. The raw materials used in the embodiments are all Xinjiang Santanghu porcelain stone, calcite and feldspar that meet the above-mentioned chemical composition requirements. The equipment used is conventional ceramic preparation equipment (stone mill, ball mill, mixer, high-temperature kiln).
[0032] Example 1 A method for preparing porcelain based on Xinjiang Santanghu porcelain stone, the specific steps of which are as follows: (1) Preparation of basic glaze: Weigh 75% Santanghu porcelain stone, 12% calcite, and 13% feldspar by mass percentage; manually select the Santanghu porcelain stone to remove mud and stone impurities, wash it with clean water until the washing liquid is clear, and dry it; crush the dried Santanghu porcelain stone, calcite, and feldspar separately with a stone mill, and control the particle size of the crushed raw materials to reach 100 mesh; put the crushed raw materials into a mixer and mix for 0.5 hours until the materials are uniform to obtain the basic glaze; (2) Glaze preparation: Deionized water was added to the base glaze, and the mixture was ground using a wet ball milling process. The mass ratio of material:ball:water was controlled at 1:2:1, and the ball milling time was 13 hours. After ball milling, the fineness of the glaze was tested using a 200-mesh standard sieve, and the residue was <0.5%. Deionized water was added to the glaze or the mixture was allowed to stand and concentrate to adjust the specific gravity of the glaze to 1.38 g / cm³. 3 Mix well and set aside. (3) Glazing: Dry the kaolin ceramic body at 80℃ for 2 hours; apply the prepared glaze slurry to the surface of the dried body using the glazing dip method, and control the glaze thickness to 0.1mm; after glazing, let the body stand for 10 minutes and drain the excess glaze slurry. (4) Firing: This is divided into five stages: First stage: The temperature is raised from 0℃ to 500℃ at a rate of 15℃ / min, and the firing is carried out in an oxygen atmosphere; Second stage: The temperature is raised from 500℃ to 1000℃ at a rate of 10℃ / min, and the firing is carried out in an oxygen atmosphere; The third stage: the temperature is raised from 1000℃ to 1300℃ at a rate of 15℃ / min, and the firing is carried out in a reducing atmosphere with a CO concentration of 1.5%. Fourth stage: After the temperature reaches 1300℃, maintain the temperature for 0.5 hours; Fifth stage: Cool to room temperature in the kiln to obtain the finished porcelain.
[0033] The product obtained in this embodiment is as follows: Figure 1 As shown, the glaze color integrates a rich variety of kiln-transformed colors such as desert, Gobi and grassland colors, without cracking, with a warm and smooth texture and a thick and lustrous glaze.
[0034] Example 2 A method for preparing porcelain based on Xinjiang Santanghu porcelain stone, the specific steps of which are as follows: (1) Preparation of basic glaze: Weigh 70% Santanghu porcelain stone, 15% calcite, and 15% feldspar by mass percentage; mechanically select the Santanghu porcelain stone to remove mud and stone impurities, wash it with clean water until the washing liquid is clear, and dry it; crush the dried Santanghu porcelain stone, calcite, and feldspar separately with a stone mill, and control the particle size of the crushed raw materials to reach 50 mesh; put the crushed raw materials into a mixer and mix for 0.5 hours until the material is uniform to obtain the basic glaze; (2) Glaze preparation: Deionized water was added to the base glaze, and the mixture was ground using a wet ball milling process. The mass ratio of material:ball:water was controlled at 1:2:1.2, and the milling time was 14 hours. After milling, the fineness of the glaze was tested using a 200-mesh standard sieve, and the residue was <0.5%. Deionized water was added to the glaze or the mixture was allowed to stand and concentrate to adjust the specific gravity of the glaze to 1.4 g / cm³. 3 Stir well and set aside. (3) Glazing: Dry the kaolin ceramic body at 50°C for 3 hours; apply the prepared glaze slurry to the surface of the dried body using the glazing dip method, and control the glaze thickness to 0.3 mm; after glazing, let the body stand for 10 minutes and drain the excess glaze slurry. (4) Firing: This is divided into five stages: First stage: The temperature is raised from 0℃ to 500℃ at a rate of 5℃ / min, and the firing is carried out in an air atmosphere; Second stage: The temperature is raised from 500℃ to 900℃ at a rate of 15℃ / min, and the firing is carried out in an oxygen atmosphere; The third stage: the temperature is raised from 1000℃ to 1300℃ at a rate of 10℃ / min, and the firing is carried out in a reducing atmosphere with a CO concentration of 2.5%. Fourth stage: After the temperature reaches 1300℃, maintain the temperature for 0.5 hours; Fifth stage: Cool to room temperature in the kiln to obtain the finished porcelain.
[0035] The product obtained in this embodiment is as follows: Figure 2 As shown, the glaze color integrates a rich variety of kiln-transformed colors such as desert, Gobi and grassland colors. It is free of cracks, has a warm and smooth texture, and is thick and lustrous. Furthermore, due to the addition of a magnetic separation iron removal step, the glaze color is more uniform.
[0036] Example 3 A method for preparing porcelain based on Xinjiang Santanghu porcelain stone, the specific steps of which are as follows: (1) Preparation of basic glaze: Weigh 80% of Santanghu porcelain stone, 9% of calcite, and 11% of feldspar by mass percentage; manually select the Santanghu porcelain stone to remove soil and stone impurities, wash it with clean water until the washing liquid is clear, and dry it; crush the dried Santanghu porcelain stone, calcite, and feldspar separately with a stone mill, and control the particle size of the crushed raw materials to reach 80 mesh; put the crushed raw materials into a mixer and mix for 0.5 hours until the materials are uniform to obtain the basic glaze; (2) Glaze preparation: Deionized water was added to the base glaze, and the mixture was ground using a wet ball milling process. The mass ratio of material:ball:water was controlled at 1:2:0.8, and the ball milling time was 14 hours. After ball milling, the fineness of the glaze was tested using a 200-mesh standard sieve, and the residue was <0.5%. Deionized water was added to the glaze or the mixture was allowed to stand and concentrate to adjust the specific gravity of the glaze to 1.5 g / cm³. 3 Stir well and set aside. (3) Glazing: Dry the kaolin ceramic body at 20°C for 4 hours; apply the prepared glaze slurry to the surface of the dried body using the glazing dip method, and control the glaze thickness to be 0.5 mm; after glazing, let the body stand for 10 minutes and drain the excess glaze slurry. (4) Firing: This is divided into five stages: First stage: The temperature is raised from 0℃ to 500℃ at a rate of 10℃ / min, and the firing is carried out in an air atmosphere; Second stage: The temperature is raised from 500℃ to 900℃ at a rate of 12℃ / min, and the firing is carried out in an oxygen atmosphere; The third stage: the temperature is raised from 1000℃ to 1300℃ at a rate of 14℃ / min, and the firing is carried out in a reducing atmosphere with a CO concentration of 2.0%. Fourth stage: After the temperature reaches 1300℃, maintain the temperature for 0.5 hours; Fifth stage: Cool to room temperature in the kiln to obtain the finished porcelain.
[0037] The product obtained in this embodiment is as follows: Figure 3 As shown, the glaze color is a rich combination of kiln-transformed colors such as desert, Gobi and grassland colors. It is crack-free, has a warm and smooth texture, and is tightly bonded to the body. Furthermore, due to the increased proportion of Santanghu porcelain stone, the regional characteristic color tone is even more intense.
[0038] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way; any equivalent transformations or modifications made based on the essence of the present invention should be covered within the protection scope of the present invention.
Claims
1. A Xinjiang porcelain enamel, characterized in that, The raw material composition and mass percentage of the Xinjiang porcelain enamel are as follows: SanTangHu porcelain stone 70%-80%; Calcite 9%-15%; White feldspar 6%-8%; The sum of the mass percentages of the raw materials is 100%.
2. A Xinjiang porcelain enamel according to claim 1, characterized in that, The SanTangHu porcelain stone comprises components with the following mass ratios: Fe2O3 2.95%, MnO 0.06%, TiO2 0.29%, CaO 10.91%, K2O 2.30%, Al2O3 5.33%, SiO2 38.80%, MgO 4.84%, and the balance being impurities.
3. A Xinjiang porcelain enamel according to claim 1, characterized in that, The calcite comprises components with the following mass ratios: CaO 55.87%, CO2 43.28%, MgO 0.27%, SiO2 0.38%, Fe2O3 0.09%, Al2O3 0.1%, and the balance being impurities.
4. A Xinjiang porcelain enamel according to claim 1, characterized in that, The white feldspar comprises components with the following mass ratios: SiO2 65.83%, Al2O3 18.94%, K2O 10.10%, Na2O 4.23%, Fe2O3 0.39%, and loss on ignition 0.51%.
5. A method for preparing porcelain using the Xinjiang porcelain enamel according to any one of claims 1-4, mainly comprising the following steps: (1) Preparation of base glaze material: after ore dressing and washing of the SanTangHu porcelain stone, the SanTangHu porcelain stone, calcite, and white feldspar are dried, and then ground to a particle size of 50-100 mesh. The ground raw materials are weighed according to the mass percentages of claim 1, mixed for 0.5 hours, and a base glaze material is obtained; (2) Preparation of the slip: add deionized water to the base glaze, and use wet ball milling process to mill for 13-14 hours to make the fineness of the slip reach 200 mesh and the residue amount <0.5%, add deionized water to the slip or conduct static concentration to adjust the specific gravity of the slip to 1.4-1.5 g / cm 3 , and reserve after uniform stirring; (3) Preparation of the glaze: add deionized water to the base glaze, and use wet ball milling process to mill for 13-14 hours to make the fineness of the glaze reach 200 mesh and the residue amount <0.5%, add deionized water to the glaze or conduct static concentration to adjust the specific gravity of the glaze to 1.4-1.5 g / cm 3 , and reserve after uniform stirring; (3) Glazing: the ceramic body is dried at 28-80℃ for 2-4 hours, and the glaze slurry is applied to the surface of the ceramic body by dipping or spraying, with the glazing thickness controlled at 0.1-0.5mm. After glazing, the ceramic body is left to stand for 10 minutes and then drained; (4) Firing: the firing process is divided into the following five stages: First stage: from 0℃ to 500℃ at a heating rate of 5-15℃ / min, and firing in an oxygen atmosphere; Second stage: from 500℃ to 1000℃ at a heating rate of 10-15℃ / min, and firing in an oxygen atmosphere; Third stage: from 1000℃ to 1300℃ at a heating rate of 10-15℃ / min, and firing in a reducing atmosphere; Fourth stage: holding at 1300℃ for 0.5 hours; Fifth stage: cooling the kiln to room temperature, and obtaining the finished porcelain.
6. A method of making porcelain according to claim 5, wherein, In step (3), the ceramic body is made of kaolin.
7. A method of making porcelain according to claim 5, wherein, In step (4), the reducing atmosphere is CO atmosphere, and the CO concentration is 1.5-2.5%.
